The Influence of Discovery Learning Model and Mastering Vocabulary in Environmental Sector to the Writing Text - Yosi Pratiwi; Harris Effendi Thahar; Irfani Basri (Fakultas Ilmu Pendidikan UNP)
This research aimed to describe the influence of discovery learning model and mastering vocabulary in environmental sector to the writing text report observation result of the students of class VII SMP N 31 Padang. The type of this research is quantitative with 2x2 factorial experimental design, the study population amounted to 248 students.Sampling is done by purposive sampling. Data collection uses two instruments, namely objective tests and performance tests. Analyzing and discussing the data descriptively with the concept of experimental research. The result of this research can be concluded that, result of skill of writing text report observation result of student having vocabulary mastery of environmental field is highest and lower, who were taught using a higher discovery learning model than students taught using conventional learning models. Furthermore, there is no interaction between model (discovery learning and conventional) with creativity (high and low) in influencing the skill of writing the text of the observation report of the students of class VII SMP Negeri 31 Padang.